Newborn morbidities and care procedures at the special newborn care units of Gandaki Province, Nepal: a retrospective study - Khim Bahadur Khadka; Nabina Koirala; Olena Ivanova; Ramchandra Bastola; Dela Singh; Kamala Rana Magar; Bidhya Banstola; Ramesh Prasad Adhikari; Vincentas Giedraitis; Deepak Paudel; Guenter Froeschl (BMC Pregnancy and Childbirth)
Abstract Background Despite recent improvements in the overall health status of Nepal’s population, newborn morbidities and mortalities have remained a challenge. This study explores the situation and care strategies for newborn health problems in the Gandaki Province of Nepal. Methods This is a retrospective hospital records analysis. A structured questionnaire was employed to collect data on socio-demographic, clinical, and outcome variables in 1,355 newborns admitted to the Special Newborn Care Unit (SNCU) between May 1, 2021, and April 30, 2022, in five hospitals within the Gandaki Province. Results Among all newborns, 60% were male, and 40% belonged to Janajati indigenous families. The mean age of mothers at the time of delivery was 24.4 years; the average birth weight of babies was 2.8 kg; and the gestational week was 38 weeks. Around 96% of births occurred in healthcare facilities. The average inpatient hospital stay was 4.7 days. The reasons for SNCU admission were newborn sepsis (51%), neonatal hyperbilirubinemia (23%), respiratory distress syndrome (18%), and low birth weight (11%). Approximately 7% of the newborns were found to have died due to various causes, including sepsis, asphyxia, and indirect medical reasons. Female newborns had a 0.45-times (CI: 0.23–0.84) lower risk of mortality compared to male newborns. Underweight newborns had 8.8 times (CI: 4.5–17.2) higher risk of death than newborns with a normal birth weight, even after adjusting for other factors like sex, delivery site, mode of delivery, mother’s age, respiratory distress syndrome, neonatal hyperbilirubinemia, neonatal sepsis, and age at admission to SNCU. The most common treatments included injectable antibiotics (73%), intravenous fluids (53%), oxygen delivery (39%), and phototherapy (36%), while 3% received “Kangaroo Mother Care (KMC)”. Conclusions The study showed that newborns suffered from multiple health complications such as sepsis, hyperbilirubinemia, or asphyxia, and many newborns received essential medical services from hospitals. Birth weight, sex of the newborn, and respiratory distress syndrome were significantly associated with neonatal mortality. Hospitals should focus on reinforcing KMC, neonatal resuscitation, and early infection control measures.